Changing Ozone (O3) in ambient air to human health: A literature review - Tanatiratorn, Nawaphorn; Panakul, Shopan; Saokleaw, Phoodit; Mungkalarungsi, Sujimon (UBRU Journal for Public Health Research, 2024)
The fluctuating ozone layers pose significant challenges to human health and the environment due to their complex interactions with pollutants and sunlight. Understanding the implications of changing ozone levels in ambient air is crucial for mitigating health risks associated with respiratory ailments and UV radiation exposure. This study aims to comprehensively review the multifaceted relationship between changing ozone levels in ambient air and their impact on human health. By synthesizing existing literature, we seek to elucidate the chemical composition and toxicity of ozone, explore the mechanisms driving changes in atmospheric ozone, and examine the diverse effects of ozone on human health. A thorough search across scholarly databases, including Science Direct, Springer, Google Scholar, NIH, and official sources of information, was conducted. The search encompassed diverse temporal periods and utilized carefully selected keywords such as 'Ozone,' 'health effects,' and 'Ambient air.' Additionally, reference lists and abstracts from international conferences on climate change and ozone dynamics were examined to ensure a comprehensive review of relevant literature. The review shed the lights of the dual nature of ozone, serving as a protective shield against UV radiation in the stratosphere while posing health risks at ground level. Factors driving changes in atmospheric ozone, including natural processes and human activities such as chlorofluorocarbon emissions and global warming, are discussed. The diverse effects of ozone on human health, ranging from increased risks of skin cancer and cataracts to impairments in lung function and exacerbation of respiratory conditions, are elucidated. Urgent action is needed to address human-induced factors contributing to ozone depletion and implement measures to safeguard both human health and the environment. Continued research into the mechanisms underlying ozone's impact on human health is essential for developing effective strategies to protect public health and mitigate the adverse effects of ozone pollution.